Web-Based Design and Development of an Arts and Culture Service System at the Jakarta Arts Center Taman Ismail Marzuki Management Unit Using the Agile Method - Asep Ubaidillah; Bertalya (Journal Research of Social Science, Economics, and Management, 2025)
In the current era, most government public services have adopted computerized and digital systems, known as e-Governance, referring to electronic technology use in various service sectors. However, after the Jakarta Provincial Government’s physical revitalization in 2022 at the Jakarta Arts Center Taman Ismail Marzuki (PKJ-TIM), the service system remained conventional. This caused slow service delivery, inadequate record-keeping, poor documentation, and limited public accessibility. To address these issues, this study aims to facilitate service access for the public and artists by transforming the PKJ-TIM Management Unit’s service system from conventional to web-based digital services. The development used the Agile methodology, enabling iterative, adaptive system development tailored to user needs. The system manages venue bookings for performance halls, supporting art and cultural activities. Key features include real-time information updates, an integrated payment gateway for secure online transactions, user feedback mechanisms, and automated digital documentation to improve transparency and access to historical data. Performance testing showed improved efficiency, faster booking processes, and higher user satisfaction. This research contributes to digital transformation literature in the arts and culture sector by presenting an Agile methodology case study in a public cultural institution. It highlights user-centered design’s importance and demonstrates how digital platforms can bridge service delivery gaps, promote inclusivity, and support Jakarta’s creative economy growth.